Sulfonamides in milk by high performance liquid chromatography with pre-column derivatization and fluorescence detection - Alaburda, Janete; Ruvieri, Valter; Shundo, Luzia; Almeida, Adriana Palma de; Tiglea, Paulo; Sabino, Myrna (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate and validate a method for analysis of sulfathiazole (STZ), sulfamethazine (SMZ) and sulfadimethoxine (SDM) residues in milk. Extraction was carried out with diclhoromethane followed by silica solid phase extraction. The extracts were derivatizated with fluorescamine and quantified by reversed-phase high performance liquid chromatography with fluorescence detection. The detection limit for the three sulfonamides was 0.3 µg L-1 and the quantification limit was 1 µg L-1 for STZ and SMZ and 2.5 µg L-1 for SDM, with coefficient of variation ranging from 4.4 to 6.6%. The recoveries for STZ, SMZ and SDM were 63.2, 91.2 and 63.2%, respectively. Considering that Brazilian regulation sets maximum residue limit in milk of 100 µg kg-1 for total sulfonamide concentrations (STZ, SMZ and SDM), the present method is adequate to quantify the residues of three sulfonamides simultaneously in UHT milk.
Keywords: fluorescamine; sulphonamides; sulfamethazine; sulfadimethoxine